2018
DOI: 10.2147/cmar.s178732
|View full text |Cite
|
Sign up to set email alerts
|

A 15-lncRNA signature predicts survival and functions as a ceRNA in patients with colorectal cancer

Abstract: PurposeColorectal cancer (CRC) is one of the most common malignant tumors worldwide. This study aimed to explore the prognostic value of lncRNAs in CRC.Material and methodsWe performed gene expression profiling to identify differentially expressed lncRNAs between 51 normal and 646 tumor tissues from The Cancer Genome Atlas database. Cox regression and robust likelihood-based survival models were used to find prognosis-related lncRNAs. A lncRNA signature was developed to predict the overall survival of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 32 publications
4
56
0
Order By: Relevance
“…In this study, we characterized that AC010789.1 was expressed at a low level in healthy tissues but a high level in CRC tissues. Also, the high expression of AC010789.1 was indicative of poor prognosis and associated with lymph node metastasis, which was consistent with previous studies (Wang X. et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we characterized that AC010789.1 was expressed at a low level in healthy tissues but a high level in CRC tissues. Also, the high expression of AC010789.1 was indicative of poor prognosis and associated with lymph node metastasis, which was consistent with previous studies (Wang X. et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…LncRNA is a transcript longer than 200 nucleotides that cannot be translated into proteins and is among the most prevalent transcriptional changes in tumour . In colon cancer, several prognostic predictive models have been developed based on lncRNAs . However, as none of them has been reported to provide potential treatment guidance, these models may not meet clinical needs.…”
Section: Introductionmentioning
confidence: 99%
“…LINC01354 is a long intergenic non‐protein‐coding RNA. Previous observations showed that LINC01354 participates in TP53 signaling pathways via hsa‐mir‐107 and hsa‐mir‐497‐5p in colorectal cancer, regulating CDK6 and CCNE1 , respectively . Notably, it was recently reported that LINC01354 dysregulation is related to genomic alterations in thyroid cancer .…”
Section: Discussionmentioning
confidence: 99%